2016
DOI: 10.1038/bmt.2016.221
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and efficacy of autologous platelet lysate drops for treatment of ocular GvHD

Abstract: Current ocular GvHD (oGvHD) treatments are suboptimal. We investigated the safety and efficacy of long-term continuous treatment with autologous platelet lysate (PL) drops in patients with oGvHD Dry Eye Syndrome (DES) score 2-3 refractory to topical conventional therapy. Ophthalmic evaluation was performed at 6 month intervals. Symptoms were assessed using the Glaucoma Symptom Scale (GSS). Patients were defined 'responders' when showing a reduction at least one grade on National Institutes of Health Eye Score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…PDGF also acts as a vital growth factor in healing soft and hard tissues wounds (Burnouf et al, 2013;Losi et al, 2015). This growth factor is also effective in regular cartilage defect (Tyrnenopoulou, Diakakis, Karayannopoulou, Savvas, & Koliakos, 2016), skin and diabetic foot ulcer repair (Civinini et al, 2013;Stacey, Mata, Trengove, & Mather, 2000), corneal repair (Pezzotta, Del Fante, & Scudeller, 2017), bone healing and bone regeneration (Torreggiani et al, 2014), and angiogenesis (Bari et al, 2018;Burnouf et al, 2013;Civinini et al, 2013).…”
Section: Pdgfmentioning
confidence: 99%
“…PDGF also acts as a vital growth factor in healing soft and hard tissues wounds (Burnouf et al, 2013;Losi et al, 2015). This growth factor is also effective in regular cartilage defect (Tyrnenopoulou, Diakakis, Karayannopoulou, Savvas, & Koliakos, 2016), skin and diabetic foot ulcer repair (Civinini et al, 2013;Stacey, Mata, Trengove, & Mather, 2000), corneal repair (Pezzotta, Del Fante, & Scudeller, 2017), bone healing and bone regeneration (Torreggiani et al, 2014), and angiogenesis (Bari et al, 2018;Burnouf et al, 2013;Civinini et al, 2013).…”
Section: Pdgfmentioning
confidence: 99%
“…Del Fante and colleagues used autologous platelet lysate mucoadhesive formulation in the treatment of oral cGvHD, and they used allogeneic blood only in patients with thrombocytopenia . Pezzotta and coworkers used autologous platelet lysate drops for treatment of ocular cGvHD . Tahmaz and colleagues demonstrated that the application of autologous serum eye drops in patients with ocular cGvHD was safe and efficient with no side effects in treatments lasting 6 months, although they collected 300 to 450 mL of autologous blood, which was twice the volume collected in our patients …”
Section: Discussionmentioning
confidence: 88%
“…In fact, PLTrich blood derivatives, such as PLT-rich plasma, PLT-rich fibrin or PLT releasate, are applied for stem cell-based tissue engineering and regeneration [30]. Moreover, the clinical use of autologous PLT products is proven in the application of PLT lysate drops to prevent graft-versus-host disease (GvHD) [31] or support wound healing in ophthalmology [32]. Hence, advantages and potential applications of PLT products are numerous.…”
Section: Discussionmentioning
confidence: 99%